TINGKAT KECERDASAN EMOSIONAL MAHASISWA DALAM PROSES PEMBELAJARAN DI MASA PANDEMIC COVID-19 DI KAMPUS STIKES GETSEMPENA LHOKSUKON - Ibrahim, Nurul; Muslim, Muslim (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Intellectual intelligence (IQ) only contributes 20% to success, while 80% is contributed by other factors, including emotional intelligence (EQ), namely the ability to motivate oneself, overcome frustration, control impulses, regulate mood (mood), empathy and the ability to work together. Getsempena STIKes students must have good emotional intelligence in order to be able to pass the educational process during the COVID-19 pandemic running smoothly and have qualified skills. The research design uses the Corelation Analysis approach. The research was conducted at the Getsempena Lhoksukon STIKes Campus which is located in the village of Ulhee Tanoh, North Aceh Regency. In this study, the researchers took a sample of 85 samples that had been selected based on the criteria determined by the researcher. Researchers can conclude that the level of emotional intelligence of STIKes Getsempena Lhoksukon students is in the bad category with a percentage of 75.3% which is caused by changes in misconceptions in the learning process, network constraints and motivation in learning. However, for the online learning process itself, students are in the good category, namely 94.1%, the researcher assumes that the lack of supervision and active interaction during the teaching and learning process causes students to only attend online lectures and feel unsupervised so they are less concerned. P Value 0.326, which means that there is no relationship between emotional intelligence and online learning during the covid-19 pandemic.